2009
DOI: 10.1002/hec.1533
|View full text |Cite
|
Sign up to set email alerts
|

Providing care for an elderly parent: interactions among siblings?

Abstract: This article is focused on children providing and financing long-term care for their elderly parent. The aim of this work is to highlight the interactions that may take place amongst siblings when deciding whether or not to become a caregiver. We look at families with two children using data from the Survey of Health, Ageing and Retirement in Europe; our sample plots 314 dependant elderly and their 628 adult children. In order to identify the interactions between siblings, we have specified a two-person discre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 25 publications
2
18
0
3
Order By: Relevance
“…The alternative caregivers are typically siblings as the use of formal care is rare (Chan, 2005;Arifin, 2006). The younger of siblings often take up the filial responsibility and care for their aging parents (Konrad et al, 2002;Fontaine et al, 2009).…”
Section: Reasons For Cohabitation and Related Literaturementioning
confidence: 99%
“…The alternative caregivers are typically siblings as the use of formal care is rare (Chan, 2005;Arifin, 2006). The younger of siblings often take up the filial responsibility and care for their aging parents (Konrad et al, 2002;Fontaine et al, 2009).…”
Section: Reasons For Cohabitation and Related Literaturementioning
confidence: 99%
“…Fontaine et al [11] also used adaptive capacity, exposure, and sensitivity elements of vulnerability to assess drought vulnerability in the state of Washington. Although they used the same elements of vulnerability as applied by Dressa et al [14], they utilized a different formula; as shown in Equation (2):…”
Section: Vulnerability Assessment Modelsmentioning
confidence: 99%
“…Naturally meaning that higher adaptive capacity leads to lower vulnerability. Fontaine et al [11] used the frequency and severity of drought to measure exposure. Furthermore, they measured sensitivity by using magnitude, duration, and the spatial extent of the drought and also applied farmers' managerial skills to measure adaptive capacities.…”
Section: Vulnerability Assessment Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the collective model, the model for adult siblings in this paper does not assume in advance that the decision process is cooperative (Pareto efficient). Some studies that consider caregiving decisions among siblings assume that decisions are made non-cooperatively (Hiedemann and Stern, 1999;Byrne et al, 2009;Callegaro and Pasini, 2008;Fontaine et al, 2009), while others assume a two-stage decision process in which siblings (1) decide whether to participate in caregiving or not, and (2) those who participate in caregiving make a cooperative care decision (Engers and Stern, 2002). This study computes cooperative as well as non-cooperative equilibria between siblings using the estimated preference parameters from the structural model, and compares these equilibria to the observed outcomes found in the data.…”
Section: Introductionmentioning
confidence: 99%